In vitro study of elephant hindgut fermentation using feed and faecal sample - Baharudin, Nabeelah Aniyyah (2017)
Both elephant and cattle are herbivorous animal that differs by site of fermentation but similar in inability of producing fibre-degrading enzyme which instead produced by the microbes in the gut. But it is appears to be that elephant have much lower daily dry matter intake than ruminant’s maintenance requirement. Hence, an in vitro gas production (GP) technique is used to study the fermentation ability and compare the rate between elephant and cattle by using faecal and rumen samples as inoculums respectively. The fresh faecal (F) and rumen (R) were collected, filtered and mixed with buffer solution before incubated in 39°C distilled water to digest 3 types of substrates which were the treatments; elephant feed (EF), Pakchong Napier grass (PN) and 50:50 mixture of both feed (M) for 72 hours. Produced gas volume (mL) were recorded every 4th hour. In Vitro Dry Matter Digestibility (IVDMD) were determined post-incubation. F versus R inoculums, higher GP recorded for FEF and FPN (0 to 20 and 24th hour respectively) but become lower than REF and RPN till incubation periods ends. FPN recorded constantly lower GP than RPN. For IVDMD, comparing with R, F inoculums obtained higher percentage for FEF and FM but lower for FPN. In conclusion, though hypothesis was rejected but this study found that elephants’ F inoculums achieved faster asymptotic gas production.